Active controller design for precision computerized numerical control machine tool systems. Issue 3 (December 2019) - Fu, Cheng-Biao; Tian, An-Hong; Li, Yu-Chung; Yau, Her-Terng
The control of a tri-axis computerized numerical control machine tool platform, which is driven by an AC servo motor is discussed in this paper. To establish a system model, the particle swarm optimization algorithm was used to transform the X–Y platform of a machine tool into a transfer function before simulation and verification of digital control was done using MATLAB. The control methods used in this study include proportional-integral-derivative control, quantitative feedback design theory and sliding mode control. They were realized with C# and the errors of motion trajectories generated by the controllers were observed. It was concluded that of the three methods studied, sliding mode control produced the lowest error rate.